Knowledge, Attitude and Practice of Tea factory Workers on Occupational health hazards and safety in selected tea factory workers of Suryadaya Municipality, Ilam. - Sapkota,Vaskar (2016)
ABSTRACT: Occupational Health Hazards refer to the potential risks to health and safety of workers in their workplaces. Tea garden workers are susceptible to a number of hazards in their workplaces due to physical, biological, mechanical, chemical and psychosocial factors.. Factors such as income, educational levels of the workers, availability of medical facilities in the tea gardens, hygiene and sanitation, general awareness and perception about the different occupational health hazards have been taken into account while arriving at the findings of the study. The study was designed to establish "Knowledge, Attitude & Practice of Tea Factory workers on Occupational health Hazards and Safety in Selected tea factory workers of Suryadaya Municipality, Ilam". Occupational Health Hazards refer to the potential risks to health and safety of workers in their workplaces. Objective: The objective of the study is to find out the level of Knowledge, attitude and Practices regarding occupational health hazard and safety among tea workers and to find out the gaps between knowledge and practices regarding occupational health and safety. Methodology: This is a descriptive cross sectional study. The study area is tea factory located at Suryadaya Municipality of Ilam; Simple random sampling was done among the tea factory. The sample size was estimated to be 95.Data was collected by using face to face interview method by student himself. The data was collected using structured as well as semi-structured questionnaire .Data was analyzed using simple descriptive statistical method. Result: It has been found from the study that the tea garden workers are educationally lagging behind, health facilities are not adequate and safety measures are lacking. This has resulted in a number of work-related accidents and the workers are found to suffer from a number of health problems. Conclusions: Occupational safety and health are key issues today, with growing industrialization and labor market. To introduce and maintain a high standard of safety and health at workplace, it is essential to have an overall picture of the present workplace scenario, different hazards and probable health effects. Keywords: Accidents, Hygiene and sanitation, Medical facilities, Occupational health hazards.